Estudo e fabricação de termistores de ZnO dopados com CU por reação de combustão com otimização de eletrodos - Carvalho Filho, Luiz Henrique de (2021)
ZnO is a material that has characteristics of a semiconductor and is used in a versatile way, which has been widely studied by the scientific community, due to its vast technological application. It is an easy-to-manufacture material and has acceptance of some chemical elements as a dopant in its atomic structure, such as Cu. When Cu replaces Zn, in the wurtzite structure of ZnO, with the aim of forming a thermistor, there is greater electrical stability to temperature increase. This work consists in the formation of a ZnO-based semiconductor, by the combustion reaction method, doped with a transition metal. In the formation of pellets, sintered at 1050°C with a level of 1h, it can be observed that ZnO, with its dopant, formed a Negative Temperature Coefficient (NTC) type thermistor and did not present a second phase. Dopant Cu increased the initial thermoelectric resistance from 1% of the dopant, while the gap size remained practically the same with doping. When Cu, entering the structure of ZnO, changes some characteristics of the element, due to a barrier in the flow of electrons, known as the Schottky barrier. Two types of electrodes for fixing the terminals to the chip were also analyzed: conductive silver-based paint and tin/lead solder; both showed a low ohmic contact, as well as good conductors of electrical current, when the terminals were fixed to the inserts.